2003
DOI: 10.1016/s0304-4203(02)00039-7
|View full text |Cite
|
Sign up to set email alerts
|

Activity coefficients in sea water using Monte Carlo simulations

Abstract: Activity coefficients in sea water using monte carlo simulations. General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…(9) is that the refractive index, the density, and the activity for seawater have all been measured with high precision as a function of salinity. The activity for seawater was recently estimated using a Monte Carlo simulation [30], the results agree with the experimental values [20] Table 1, which also listed the formulae for the other parameters in Eqs (2) and (9).…”
Section: Introductionsupporting
confidence: 67%
“…(9) is that the refractive index, the density, and the activity for seawater have all been measured with high precision as a function of salinity. The activity for seawater was recently estimated using a Monte Carlo simulation [30], the results agree with the experimental values [20] Table 1, which also listed the formulae for the other parameters in Eqs (2) and (9).…”
Section: Introductionsupporting
confidence: 67%
“…This property is typically derived from a thermodynamic model such as Pitzer's [65], with the model itself fit to vapor pressure data or boiling point elevation data. In the literature, the activity of water in seawater was reported previously by Bromley et al [33] and by Lund et al [66]. Bromley et al, calculated activity using a model fit to boiling point elevation data and reported data for 0 ≤ t ≤ 200 °C and 10 ≤ S ≤ 120 g/kg while Lund used statistical mechanics to calculate activity for t = 25 °C and 5 ≤ S ≤ 35 g/kg.…”
Section: Appendix D Activity Of Water In Seawatermentioning
confidence: 96%
“…The departure from ideality (γ = 1) is nonnegligible and as a consequence the dissolution of CO 2 in sea water is significantly larger than in fresh water. The excellent agreement between measured and simulated activity factors in Table 1 0.14 0.15 Table 1: Experimental [5,6] and simulated [7] mean activity factors in sea water at 298 K. The salinity is 3.5 %.…”
Section: A Simple Electrolyte Solutionmentioning
confidence: 75%